2021
DOI: 10.1007/s12022-021-09667-0
|View full text |Cite
|
Sign up to set email alerts
|

What Did We Learn from the Molecular Biology of Adrenal Cortical Neoplasia? From Histopathology to Translational Genomics

Abstract: Approximately one-tenth of the general population exhibit adrenal cortical nodules, and the incidence has increased. Afflicted patients display a multifaceted symptomatology-sometimes with rather spectacular features. Given the general infrequency as well as the specific clinical, histological, and molecular considerations characterizing these lesions, adrenal cortical tumors should be investigated by endocrine pathologists in high-volume tertiary centers. Even so, to distinguish specific forms of benign adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 201 publications
(332 reference statements)
2
55
0
2
Order By: Relevance
“…The 2022 WHO classification no longer endorses the use of "nodular adrenal cortical hyperplasia" for incidentally discovered sporadic non-functional adrenal cortical nodules. The latter stems from recognition of the clonal/neoplastic nature of incidentally discovered non-functional subcentimeter benign adrenal cortical nodules [1][2][3][4][5]. The new classification endorses the term sporadic nodular adrenocortical disease for such manifestations (Fig.…”
Section: Question 1: Are There Any Nomenclature Changes or Any New Di...mentioning
confidence: 99%
“…The 2022 WHO classification no longer endorses the use of "nodular adrenal cortical hyperplasia" for incidentally discovered sporadic non-functional adrenal cortical nodules. The latter stems from recognition of the clonal/neoplastic nature of incidentally discovered non-functional subcentimeter benign adrenal cortical nodules [1][2][3][4][5]. The new classification endorses the term sporadic nodular adrenocortical disease for such manifestations (Fig.…”
Section: Question 1: Are There Any Nomenclature Changes or Any New Di...mentioning
confidence: 99%
“…This correlation further supports the hypothesis of different clinicopathological groups of PBMAH as recent progress in other type of adrenal tumors have suggested. 21 This study identified the lysine-specific demethylase 1 gene KDM1A (also known as lysine-specific histone demethylase 1A gene LSD1) as a tumor suppressor gene responsible for the genetic predisposition to PBMAH associated with FDCS. A germline KDM1A variant was observed in 9 of 10 index cases of the patients with FDCS investigated in this study (in 5 of 6 patients of the 36 patients investigated in the integrated genomics study and in 4 of 4 additional index patients subsequently investigated specifically for KDM1A alteration).…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with CND, one in 10 adults has a tumor at the level of the adrenal cortex, mostly an age-dependent, so called 'adrenal incidentaloma' (44). Adrenal tumor-related genetic backup is identified with regard to channel anomalies as found in some cases of primary hyperaldosteronism; in TP53 mutations (such as Li-Fraumeni syndrome) causing adrenocortical carcinoma, especially in pediatric individuals, or pigmented adrenal lesions induced by CNC (45,46). Other syndromic circumstances associated with an adrenal tumor involves multiple endocrine neoplasia type 2A, neurofibromatosis type 1, McCune-Albright syndrome, Beckwith-Wiedemann syndrome, and von Hipple-Lindau disease (47).…”
Section: Adrenal Diseasementioning
confidence: 99%